(untitled) (Teaching and Learning Inquiry, 2020)
This article examines the experiences of students after completing an online postgraduate learning technologies applications course with respect to the transfer of learning of skills, knowledges, and perspectives to their professional educational practice. Transfer of learning was perceived to have occurred with respect to overall course design and specific learning activities. Transfer of learning from the course to educational practice was seen as effective for most study participants; however, the strong community of practice inculcated within the course eroded after the course ended.